An exploratory comparative study in achievement motivation between Malay and Australian secondary school students. - Wan Rafaei Abdul Rahman (Universiti Kebangsaan Malaysia, 1972)
The study was conducted to investigate the achievement motivation of Muslim Malay secondary school students compared with that of Catholic Australian secondary students. Two methods of measuring achievement motivation, the Mehrabian Achievement Scale (MAS) and the Thematic Apperception Test (TAT) were administered to the Malay subject (from English Medium (EM) and Malay Medium (MM) schools) and the Australian subject (AS). The results indicated that there was a significant difference in achievement motivation between the Malay and Australian subjects. However, the direction of the difference on one scale was the reverse in the case of the other. The differences in the results obtained and the efficacy of the two scale were discussed.